Challenges and opportunities for non-antibody scaffold drugs. Issue 10 (October 2015) - Vazquez-Lombardi, Rodrigo; Phan, Tri Giang; Zimmermann, Carsten; Lowe, David; Jermutus, Lutz; Christ, Daniel
Highlights Non-antibody scaffold drugs are a promising new class of biologics drugs. The first candidate scaffolds are now moving into clinical development and practice. Challenges remain and scaffolds will need to be further tailored toward applications where they provide real advantages over established therapeutics to succeed in a rapidly evolving drug development landscape.